Investigating the Use of Project-Based Learning Using Animated Video Media in English Learning, Writing Descriptive Text at Vocational High School Students - Naufal Syafiqri (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines the implementation of Project-Based Learning using animated videos in teaching descriptive writing to vocational high school students and explores students' experiences with this integrated approach. Using a case study design, data were collected through observations and interviews with teachers and students. The results of the study indicate that teachers successfully implemented a structured project-based learning approach, beginning with an explanation of the material, followed by the screening of animated videos, group discussions for text writing (planning, drafting, editing, and final presentation), and reflection. The animated video